Răspuns :
x supra 4 - 1 supra 5 = 3 supra 10
x supra 4 =3 supra 10 + 1 supra 5 (amplificam cu 2 pe 1 supra 5)
x supra 4 =3 supra 10 + 2 supra 10
x supra 4 =5 supra 10
x * 10 =4 * 5
x * 10 = 20
x = 20 : 10
x = 2
Sper ca te-am ajutat ! PS * este inmultire.
x supra 4 =3 supra 10 + 1 supra 5 (amplificam cu 2 pe 1 supra 5)
x supra 4 =3 supra 10 + 2 supra 10
x supra 4 =5 supra 10
x * 10 =4 * 5
x * 10 = 20
x = 20 : 10
x = 2
Sper ca te-am ajutat ! PS * este inmultire.
X supra 4=3 supra 10 +1 supra 5 x supra 4=5supra 10 x=5x4supra 10 =>x=2